2013
DOI: 10.5194/acpd-13-4863-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and seasonal distribution of Arctic aerosols observed by CALIOP (2006–2012)

Abstract: We use retrievals of aerosol extinction from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) on board the CALIPSO satellite to examine the vertical, horizontal and temporal variability of tropospheric Arctic aerosols during 2006–2012. We develop an empirical method that takes into account the difference in sensitivity between daytime and nighttime retrievals over the Arctic. Comparisons of the retrieved aerosol extinction to in situ measurements at Barrow (Alaska) and Alert (Canada) show that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The composition and effects of aerosol are extremely important to understand in the Arctic, which is warming faster than any other region of the world (Stocker, 2014). Long‐range transport from lower latitudes can be an important source of aerosol; however, in the summertime wet removal results in less efficient transport of aerosol, meaning that the Arctic atmosphere can be characterized as relatively clean near the surface (Croft et al, 2016; Di Pierro et al, 2013; Polissar et al, 1999). In periods with no influence from transport, aerosol numbers are strongly influenced by new particle formation and growth (NPF/G), which has been shown to control the concentration of CCN in the Arctic (Croft et al, 2016; Heintzenberg et al, 2017; Köllner et al, 2017; Leaitch et al, 2013; Willis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The composition and effects of aerosol are extremely important to understand in the Arctic, which is warming faster than any other region of the world (Stocker, 2014). Long‐range transport from lower latitudes can be an important source of aerosol; however, in the summertime wet removal results in less efficient transport of aerosol, meaning that the Arctic atmosphere can be characterized as relatively clean near the surface (Croft et al, 2016; Di Pierro et al, 2013; Polissar et al, 1999). In periods with no influence from transport, aerosol numbers are strongly influenced by new particle formation and growth (NPF/G), which has been shown to control the concentration of CCN in the Arctic (Croft et al, 2016; Heintzenberg et al, 2017; Köllner et al, 2017; Leaitch et al, 2013; Willis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, significant progress in characterizing the tropospheric aerosol vertical distribution has been made in the recent years through the use of ground‐ and satellite‐based lidar measurements, especially those from the Cloud–Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) satellite that has been acquiring cloud and aerosol backscattering data since mid‐June 2006 [ Winker et al , ]. The CALIOP Level 2 Layer 5 km product [ Liu et al , , ; Omar et al , ; Vaughan et al , , ] has been used in previous studies to assess the 3‐D distribution of tropospheric aerosols from regional to global scales [e.g., Yu et al , ; Koffi et al , ; Sheridan et al , ; Di Pierro et al , ; Winker et al , ; Prijith et al , ]. Despite several limitations (see, for instance, Koffi et al [], Winker et al [ ], Young et al [], and Kim et al []), the version 3.01 product [e.g., Hu et al , ; Liu et al , ; Vaughan et al , ] was shown to provide a realistic and representative description of the mean regional vertical distributions and seasonal variations of aerosol extinctions, over source and downwind regions.…”
Section: Introductionmentioning
confidence: 99%
“…Verzella, 2008). Pollution and dust from Asian sources can reach the Arctic in 3 to 5 days, carried by mid-latitude cyclones (Di Pierro et al, 2011;Di Pierro et al, 2013;. In the earlier CALIOP data product releases, dust layers over the Arctic could be misclassified by the CAD algorithm as ice clouds (Di Pierro et al, 2011).…”
Section: B Lofted Asian Dust Layers Near the Arctic 25mentioning
confidence: 99%